The Relationship Between the Time Spent on Facebook and GPA Scores of Post-Graduates - Rahim, Mohammad Naim (Future Science / FSH-PH Publications, 2021)
The article is aimed to study the correlation between the time spent on Facebook and GPA scores of post-graduate students of Afghanistan. Facebook, WhatsApp, Telegram, and many other social networks are used broadly by scholars inside and outside the campuses. However, these social platforms are a mean for communication and have paved the way for interactive educational practices, but still there are concerns on the relationships of these social applications on students’ educational developments. Reviewing the literature, the study identified that there are few articles on the impact of social media on teaching and learning in Afghanistan which are conducted in different context as well as applied different methods and observations. Therefore, this article intended to use a quantitative approach and descriptive survey to evaluate the GPA scores of the students and the time spent on Facebook in order to evaluate their relationships. The data is analysed performing Repeated Measure ANOVA and Pearson Correlation. The results show that there is no significant difference in the mean score of GPAs between three semester of post-graduates. It also highlights that there is no correlation between the time spent on Facebook and the GPA scores of students. To conclude, the study contributes to enrich the ongoing e-learning strategies of the higher education by underlining the potentials and restrictions of the use of social medias on students’ educational developments.